ChemInform Abstract: Direct and Site‐Selective Palladium‐Catalyzed C‐7 Acylation of Indolines with Aldehydes. Issue 26 (June 2015) - Shin, Youngmi; Sharma, Satyasheel; Mishra, Neeraj Kumar; Han, Sangil; Park, Jihye; Oh, Hyunji; Ha, Jimin; Yoo, Hyunwu; Jung, Young Hoon; Kim, In Su
Abstract The use of alcohols as acyl equivalents is also possible.